Chitin-Glucan Supplementation Altered Gut Microbiota and Improved Postprandial Metabolism in Subjects at Cardiometabolic Risk. (14th June 2022) - Ranaivo, Harimalala; Zhang, Zhengxiao; Alligier, Maud; Van Den Berghe, Laurie; Sothier, Monique; Lambert-Porcheron, Stéphanie; Feugier, Nathalie; Cuerq, Charlotte; Machon, Christelle; Neyrinck, Audrey; Seethaler, Benjamin; Rodriguez, Julie; et al.
Abstract: Objectives: In this exploratory study, we aimed at characterizing the impact of chitin-glucan (CG), an insoluble dietary fiber, on gut microbiota composition and functions as well as on the cardiometabolic profile in subjects at cardiometabolic risk. Methods: Fifteen subjects were included in this double-blind, randomized, twice 3-week cross-over study and consumed 4.5g of CG or maltodextrin (control) as a supplement daily. Before and after the intervention phases, fasting and postprandial metabolic parameters and exhaled gases (hydrogen [H2 ] and methane [CH4 ]) were evaluated. Gut microbiota composition (16S next generation sequencing), fecal concentrations of bile acids, long- and short-chain fatty acids (LCFA, SCFA), zonulin, calprotectin and lipopolysaccharide binding protein (LBP) were analyzed. Results: Compared to control, CG supplementation increased exhaled H2 following an enriched-fiber breakfast ingestion and decreased postprandial glycemia and triglyceridemia response to a standardized test meal challenge served at lunch. Of note, the decrease in postprandial glycemia was only observed in subjects with higher exhaled H2, assessed upon lactulose breath test performed at inclusion. CG decreased a family belonging to Actinobacteria phylum and increased 3 bacterial taxa: Erysipelotrichaceae UCG.003, Ruminococcaceae UCG.005 and Eubacterium ventriosum group . Fecal metabolites, inflammatory and intestinal permeability markers did not differ between groups. Conclusions: We showed that CG supplementation modified the gut microbiota composition and improved postprandial glycemic response, an early determinant of cardiometabolic risk. Our results also suggest breath H2 production as a non-invasive parameter of interest for predicting the effectiveness of dietary fiber intervention. Funding Sources: The FiberTAG project was initiated from a European Joint Programming Initiative "A Healthy Diet for a Healthy Life" (JPI HDHL). This study was supported by the Service Public de Wallonie. NMD is a recipient of a grant from Belgium National Scientific Research Fund and from UCLouvain. GGM is a recipient of a FSR grant from the UCLouvain.